1970
DOI: 10.2307/1933969
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Regulation of Red Squirrel (Tamiasciurus Hudsonicus) Populations

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
122
1
8

Year Published

1973
1973
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(155 citation statements)
references
References 19 publications
8
122
1
8
Order By: Relevance
“…The key role of ripening seed Nearly 40 years ago Kemp & Keith (1970) found that the reproduction of American red squirrels, and the survival of their young, improved in springs that followed winters of poor crops of spruce cones, and immediately preceding heavy crops in the following winters. Spruce cones are initiated during the previous season's flowering and the squirrels were feeding on the flower buds and developing fruit.…”
Section: An Alternative Explanationmentioning
confidence: 99%
“…The key role of ripening seed Nearly 40 years ago Kemp & Keith (1970) found that the reproduction of American red squirrels, and the survival of their young, improved in springs that followed winters of poor crops of spruce cones, and immediately preceding heavy crops in the following winters. Spruce cones are initiated during the previous season's flowering and the squirrels were feeding on the flower buds and developing fruit.…”
Section: An Alternative Explanationmentioning
confidence: 99%
“…Significant annual variations in pregnancy rate are common for red squirrels in western North America. The percentage of adult females breeding increased from 67 per cent to 88 per cent over a 1-year period in Alberta (Kemp and Keith, 1971) and decreased from 83 per cent to 32 per cent over a 1-year period in British Columbia (Smith, 1968).…”
Section: Reproduction In the Red Squirrel (Tamiasciurus Hudsonicus) Imentioning
confidence: 97%
“…Information on reproduction of the red squirrel (Tamiasciumrs hudsonicus) can be gleaned from studies in the northeastern United States (Klugh, 1927;Hamilton, 1939;Layne, 1954) and in western Canada (Miller, 1970;Smith, 1968;Kemp and Keith, 1971;Wood, 1967). However, there is a paucity of information on reproduction from the mountainous regions of the western United States.…”
Section: Reproduction In the Red Squirrel (Tamiasciurus Hudsonicus) Imentioning
confidence: 99%
See 2 more Smart Citations